2012
DOI: 10.3748/wjg.v18.i38.5351
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of Lacto-Wolfberry in a mouse model of experimental colitis

Abstract: These results demonstrate the anti-inflammatory properties of LWB and suggest that the underlying mechanism is at least in part due to NF-κB inhibition and improved anti-oxidative capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Lycium barbarum polysaccharides (LBP) protects the small intestinal structure and contributes barrier function in the intestinal damage induced by ischemia reperfusion . A milk‐based Goji preparation exerted protective roles in 2,4,6‐trinitrobenzene sulfonic acid (TNBS)‐induced colitis . Dietary Goji ameliorated IBD symptoms in dextran sulfate sodium (DSS)­induced colitis mice accompanied with decreased neutrophil infiltration and suppressed inflammatory responses…”
Section: Introductionmentioning
confidence: 96%
“…Lycium barbarum polysaccharides (LBP) protects the small intestinal structure and contributes barrier function in the intestinal damage induced by ischemia reperfusion . A milk‐based Goji preparation exerted protective roles in 2,4,6‐trinitrobenzene sulfonic acid (TNBS)‐induced colitis . Dietary Goji ameliorated IBD symptoms in dextran sulfate sodium (DSS)­induced colitis mice accompanied with decreased neutrophil infiltration and suppressed inflammatory responses…”
Section: Introductionmentioning
confidence: 96%
“…It also has been documented that WOL polysaccharide fractions can protect against renal damage 29 and reduce immunotoxicity 30 . It has been previously reported that a milk-based WOL preparation can suppress 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis 31 and WOL can suppress dextran sulfate sodium (DSS)induced colitis 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying these outcomes remains unclear, due to the complexity of the pharmacology of buprenorphine, as a non‐selective, mixed partial agonist and antagonist to the opioid receptors . Indeed, as a partial agonist of the μ‐opioid receptor, buprenorphine might be expected to ameliorate colitis, since activation of this pathway was beneficial in several models of visceral disease including TNBS, DSS, and ischemia/reperfusion injury . Furthermore, TNBS‐colitis was significantly more lethal in μ‐opioid receptor knock‐out mice, although the histological and morphological inflammatory scores were similar to control mice that received TNBS .…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were conducted on adult male mice weighing 20-25 g (BALB/c) or [30][31][32][33][34][35]. All mice had ad libitum access to food and water and were maintained on a 12:12-hour light:dark cycle at an ambient temperature of 23°C and 25%-40% relative humidity.…”
Section: Animalsmentioning
confidence: 99%